The Development of Residential Segregation among Ethnic Chinese and the Factors Sustaining their Presence in Palembang's Historic Chinatown - Tasya Rifanka; Muhammad Izzudin (SOCIUS, 2026)
The segregation of Chinese ethnic settlements in various Indonesian cities has become a persistent phenomenon despite the abolition of colonial spatial separation policies since 1910. Research on the persistence of this segregation remains limited, particularly in revealing the socio-cultural dynamics that cause Chinese communities to remain in colonial heritage areas. This study examines the formation process of Chinese ethnic settlement segregation in Kampung Kapitan Palembang from the pre-colonial era to the present, as well as the factors that cause this community to maintain cross-generational settlements. The approach used in this research is a qualitative approach with a case study research type. The selection of informants using purposive technique, totaling 16 informants consists of Chinese ethnic residents and Chinese ethnic leaders. Data were collected through observation, documentation, and literature study. This research was analyzed using the Settlement Development Theory by Griffith Taylor and the concept of settlement development factors according to Sumaatmadja. The research results show that the Chinese settlement in Kampung Kapitan was formed since the fall of the Sriwijaya Kingdom (1478) when the Ming Dynasty of China established a trading office in Palembang, then developed through four stages to the contemporary era. The persistence of this segregation is caused by collective inherited house ownership that is difficult to sell due to potential intergenerational conflicts, proximity of location to markets where they trade, strong kinship relations, daily use of Mandarin language, preservation of Chinese cultural traditions, and the designation of Kampung Kapitan as a Cultural Heritage Site.